Future directions in the treatment of pelvic fractures with abdominal organ injury: the potential of combined endovascular embolization and external fixation techniques - Ma, Ge; Di, Zhenpeng; Wen, Yonglin; Zhang, Chao; Hao, Huaxin; Li, Yukan; Zhang, Yinjun (Frontiers in Medicine, 2025)
Pelvic fractures with abdominal organ injuries are complex and life-threatening conditions that pose significant challenges in trauma care. Current management strategies, including external fixation and interventional radiology techniques such as embolization, have shown promise in stabilizing the pelvis and controlling hemorrhage. However, these approaches face challenges such as the lack of standardized protocols, variability in patient selection, and the need for robust multidisciplinary collaboration. Additionally, the combined use of these modalities may lead to improved outcomes, including reduced mortality and shorter hospital stays, but further research is needed to optimize their application. This review aims to comprehensively explore the potential synergies between endovascular embolization and external fixation in managing these complex injuries. It critically assesses the latest clinical evidence, identifies gaps in current practices, and proposes future directions to enhance treatment effectiveness and patient outcomes.